A.QOSIMOV, M.QOSIMOVA MUALLIFLIGIDAGI “INGLIZCHA-O‘ZBEKCHA-RUSCHA, O‘ZBEKCHA-INGLIZCHA-RUSCHA” ANATOMIK TERMINLAR LUG‘ATINING TUZILISH TAMOYILLARI - Ruzimov, Sh.S. (SCIENCE and SOCIETY, 2023)
In this article compiling principles of English-Uzbek-Russian (A. Qosimov, M. Qosimova) dictionary were investigated and shown its advantages and disadvantages with examples Practical recommendations are presented for improving compiling principles of the next generation of dictionaries were worked out.